Purple-Blue Pigmentation Production as a Sign of Immune Response by Bleached Corals to Avoid Stress Caused by Elevated Sea Surface Temperature - Ramesh, CH; Koushik, S; Shunmugaraj, T; Murthy, M.V Ramana (International Journal of Hydrology Research, 2019)
Coral reefs are extensively studied around the world with regard to their taxonomy, distribution, diversity, bleaching events, diseases, conservation, and restoration aspects. However, exhibition of blue pigmentation by corals under certain stressed condition such as high temperature and bleaching events has not been widely investigated. In the present study, during a massive bleaching event of coral reefs in 21 islands of Gulf of Mannar Marine Biosphere Reserve, corals such as Acropora sp. and Turbinaria sp. and some other encrusting corals have displayed purple blue pigmentation in response to high temperature and to avoid complete bleaching of their food supplying symbiotic zooxanthellae. This documentation from this environment is being reported for the first time and thus further immunological and genomic studies are required to study the variation in the zooxanthellae in bleached and non-bleached corals as well as blue pigment showing and non-pigmented corals. The compound responsible for blue pigmentation is needed to be analyzed further which could be employed for other industrial and biomedical applications.